On/Unstained White dress(es) - Anna Kasafi Perkins (African Journal of Gender and Religion (AJGR))
There is a white dress – baptismal, communion or confirmation – that appears in select poems of three Caribbean women poets, Jennifer Rahim (Trinidad), M. NourbeSe Philip (Trinidad/Canada) and Barbara Ferland (Jamaica). The dress is intended to be worn by Afro-Caribbean girls in a church, sacred, or sacramental context and speak to matters of purity in the female/girl child who is so clad. At the same time, the dress - spotless or yellowed - exposes the impurity, danger, and impiety of the Afro-Caribbean female body that is laid bare in the sacramental and sacred space of Church. This article will explore the experience of “sacred misogynoir” as expressed in Rahim, Philip, and Ferland via the symbolism of the (unstained) white dress. Drawing on the work of C. M. Webster, which unveils how Christian practices exiled Afro-Caribbean women from human and feminine value systems, I draw attention to how these women counter such disvaluing with bodily practices that promoted, (re)valued, and affirmed their body-selves, especially in sacred spaces. Webster’s research, in conversation with these poets, illustrates the need for a reframing and revaluing of the Afro-Caribbean female body in sacred spaces such that white dresses no longer function to oppress and devalue.